Climate for changing lenses: Reconciliation through site-specific, media arts-based environmental education on the water and climate change nexus in South Africa and Canada - Van Borek, Sarah (Rhodes University, Faculty of Education, Department of Education)
This study took place in the context of a growing racialised global water crisis and increasing demands worldwide for transforming higher education at institutions of ongoing settler colonialism. It presents a conceptualisation of what education, research and activism can look like and unfolded inside a doctoral research project that expands what doctoral education can look like. Using a media arts-based praxis process, I developed a relational model of university curriculum "“site-specific, media arts-based, environmental education "“with potential to cultivate relations (human and nonhuman) towards reconciliation while contributing to justice at the water-climate change nexus. My aim as a settler-ally was to expand my teaching and curriculum practices, thereby also offering curriculum transformation inspiration to others. My research was rooted in my concept of reconciliation as a practice towards thriving together, where the 'together' was inclusive of both humans and nonhumans. The curriculum engaged students in de/re/constructing water narratives through making site-specific videos focused on local water bodies. Decolonising artistic approaches known as slow media and soundscape recording were strategically incorporated into audio/video mapping assignments where students observed water aesthetics in ways that shifted their perceptions about water and entities entangled with it. Students met with Knowledge Keepers (Indigenous and non-Indigenous people from outside the academy with existing relationships to water bodies). A photovoice methodology was used in these meetings with Knowledge Keepers to reconfigure traditional film director-subject power relations. Guest lecturers from non-traditional backgrounds contributed diverse perspectives. Ecomotricity was incorporated, whereby students were in deliberate movement in/with water bodies through canoeing together. The curriculum culminated in a public screening/education event where resulting videos, interspersed with educational games facilitated by students, surfaced emotions, knowledge co-production and new synergies amongst the event's temporary community. Through two iterations of the curriculum, where I co-designed and taught a course called Making Waveforms, one in Vancouver, Canada and one in Cape Town, South Africa, I explored the primary research question: How can a relational site specific, media arts-based university environmental education curriculum cultivate students' relational sensibilities and abilities oriented towards reconciliation of diverse peoples and ecosystems in South Africa and Canada? Iterating the curriculum across these two contexts allowed me to assess which aspect(s)of the curriculum may have been applicable across these and other contexts. By using mixed methods of data collection and sharing throughout the research journey, I explored the sub-questions: a) How is reconciliation understood currently by university students in South Africa and Canada? and b) How can a relational site-specific, media arts-based university environmental education curriculum and my PhD methodologies (PhD-by-publication, website, and participatory approaches to podcasting, video making, and song creation), contribute to decolonising higher education, and thereby further contribute to reconciliation of diverse peoples and ecosystems in South Africa and Canada? Integral to my praxis process, I undertook a PhD-by-publication that involved writing four academic journal articles, with each paper presenting a key stage in the process. The papers, all of which have been submitted to peer-reviewed academic journals, form part of this thesis and can be found in the Appendices. The course was originally developed around Donati's (2011) relational sociology and Gergen's (2009) relational education theory. Throughout my praxis process, I expanded my theoretical influences as called for by the research and teaching practice. The journey behind my first PhD paper, (Towards) Sound research practice: Podcast-building as modeling relational sensibilities at the water-climate change nexus in Cape Town, began when I officially started my doctoral studies in early 2018. The paper was co-authored with a fellow PhD scholar from Rhodes University's Environmental Learning Research Centre (ELRC), Anna James. It presents an experimental arts-based methodology we co-developed for doing contextual profiling by building a socially-engaged podcast series, called Day One, to explore the lived experiences of the Cape Town water crisis of 2018. It includes my initial tool of analysis for exploring how the curriculum might cultivate relational sensibilities and abilities towards reconciliation. The podcast pedagogy offered opportunities to develop some relational learning processes. The analytical tool was developed from cross-referencing reconciliation and relational educational theories. This paper also incorporated theories in relational solidarity and social movement learning. The podcast episodes included personal narratives that, in turn, revealed diverse ideologies and polarisations in the water situation. Working with the audio medium highlighted possibilities for creating and shifting affective relations. Recording and editing soundscapes of waterbodies began explorations of the agential qualities of water. These were foundational dynamics to explore in building the reconciliation curriculum. The paper is published in the International Journal of New Media, Technology, and the Arts (2019, Volume14, Issue1). My second PhD paper, A media arts-based praxis process of building towards a relational model of curriculum oriented towards reconciliation through water justice, presents my methodology for and analysis of a pilot course I co-designed and taught at the Emily Carr University of Art + Design (ECUAD) in Vancouver, Canada in 2018. This course served as contextual profiling around the water situation in Vancouver. The course was offered in partnership with a science-based environmental non-profit called the David Suzuki Foundation and an Indigenous-led post-secondary school called the Native Education College. The course's public event was hosted at the Beaty Biodiversity Museum. At this stage, I was introduced to Cree/Métis filmmaker, Gregory Coyes, and his Indigenous cinematic narrative approach known as Slow Media. Integrating slow media into video mapping assignments presented exciting possibilities for shifting views and valuing of water. This was the stage at which my concept of reconciliation expanded to explicitly include nonhumans. I applied my initial analytical tool to the curriculum here, which revealed the three most prominent relational sensibilities and abilities towards reconciliation cultivated by students through the course: (1) knowledge ecologies; (2) a hopeful social imaginary; and (3) embodied ways of knowing. I began to make connections between the curriculum and Mi'kmaq elder Albert Marshall's concept of 'Two-Eyed-Seeing', and expanded the notion to 'Three-Eyed-Seeing' to include artistic approaches. Deeply inspired by Bekerman and Zembylas's (2012) Teaching Contested Narratives, I began to see the growing importance of the narrative aspects of reconciliation education. The paper is published in the University of Pretoria's Journal of Decolonising Disciplines (2021, Volume 1, Issue 2). My third PhD paper, Water as artist-collaborator: Posthumanism and reconciliation in relational media arts-based education, presents a 2019 iteration of the curriculum at ECUAD in Vancouver, and illustrates my shift to include posthuman theories in my analysis. This course was offered in affiliation with the David Suzuki Foundation, and in collaboration with the Native Education College. The culminating public event was hosted by the Beaty Biodiversity Museum. Decentring the human in this data analysis better supported my research and curricular aims. The strong technoculture of the media arts-based curriculum fits well with many posthuman concepts. This posthuman reading of the course and data enabled me to see what changes were emerging through student-water-technology intra-actions, and how these supported relations towards reconciliation as well as water justice. Most notable of these changes was the emergence of water's agential qualities, specifically of water as becoming collaborator in artistic/knowledge co-production, where students think with water. I argued this contributes to reconciliation by decentring the human, enabling relations in which power is more equal, and where there are greater possibilities for mutual responsibility between related entities. This is where I developed the concept of audio/video as relational texts, supporting the creating and shifting of affective relations more than the monumentalised verbal/written knowledge of traditional universities. This is also where I realised that relational work towards reconciliation would require engaging with the hidden curriculum of institutions. The paper is published in the journal Reconceptualizing Educational Research Methodology (2021, Volume 12, Issue 1), as part of a special issue on Posthuman Conceptions of Change in Empirical Educational Research. My fourth PhD paper, originally entitled Making waveforms: Implicit knowledge representation through video water narratives as decolonising practice towards reconciliation in South Africa's higher education, presents an analysis of the 2019 iteration of the curriculum in South Africa. I co-designed and led a course called Making Waveforms at the University of Cape Town's Future Water Institute (FWI) in collaboration with Rhodes University. The course was co-designed/facilitated with FWI's Research Fellow Amber Abrams, who also co-authored this paper. The course's public event was hosted by a non-profit organisation called the Tshisimani Centre for Activist Education. This paper explored the ways that non-verbalisable, implicit learning "“understood as part of many non-Euro/Western ways of knowing"“ takes place in the Making Waveforms course and how this influenced water-specific climate behaviours while contributing to decolonised reconciliation practice for higher education institutions. Drawing on theories of implicit and explicit knowledge, we first showed how implicit learning primarily took place through: 1) site-specific audio/video mapping of water bodies; 2) meetings with Knowledge Keepers; and 3) an interactive public screening event. We highlighted how this non-verbalisable learning produced feelings of empathy for diverse peoples and waterways, as well as aesthetic appreciation of water, and how this can contribute to more response-able water behaviours. This, we argued, supported the valuing of implicit knowledge within a traditional educational setting, thereby pluralising knowledge, and was key to reconciliation/decolonisation in higher education. Iterating the curriculum for the South African context emphasised the importance of context-specificity of the course overall, and also of the relational work embedded in the curriculum. This paper is under review by the University of Toronto's journal Curriculum Inquiry (CI). Following receipt of CI's internal review process, the title of the paper has since been updated to Non-verbalisable, implicit knowledge through cellphilms as decolonised reconciliation practice towards response-able water behaviours in South Africa. Through reflective analysis of my four papers, I developed a concept for an Anatomy of Decoloniz/sed Curriculum consisting of five key parts: 1) relationality; 2) multimodality; 3) narratives/counter-narratives; 4) context-specificity; and 5) unhidden curriculum. Four meta reflections have been included in this thesis, each corresponding with one of the four papers, and presented chronologically according to the stage of the praxis process with which they correspond. In these meta reflections, I applied Kolb's (1984) Experiential Learning Cycle model for reflective writing, based on the premise that through experiences we can expand our understanding, and included four key stages: 1) concrete experience; 2) reflective observation; 3) abstract conceptualisation; and 4) active experimentation. For the concrete experience, I provided a thick description of my process in writing the paper, as well as aspects of the phase in my praxis process that was the focus of the paper, not included in but relevant to the paper. For the reflective observation, I identified any aspects of the experience that were new to me and which therefore presented opportunities for me to learn. For the abstract conceptualisation, I critically analysed my concrete experience and reflective observation to determine which, if any, of the five key parts of the Anatomy of Decoloniz/sed Curriculum that I outline in my introduction relate to this phase of my PhD praxis process. For the active experimentation, I made conclusions about the extent to which this phase of my PhD embraced decoloniality in practice, and built on this new understanding to make recommendations for myself and others committed to the decolonial project as part of my contribution to knowledge. These meta reflections also invite readers to follow my personal narrative of becoming-with water, meaning my transformation from being water illiterate to embracing a 'watershed mind' (Wong,2011). Multimodality, which I propose as a key part of an Anatomy of Decoloniz/sed Curriculum, is embedded in the representational aspects of this thesis. The courses I co-designed and taught as part of this project resulted in the creation of 20 short student films. My contextual profiling involved a podcast methodology that was ongoing throughout my study, as a model of decolonised research-communication-education-action at the water-climate change nexus. This methodology resulted in the creation of four Day One podcast episodes, co-produced with a PhD colleague, Anna James. Some of these episodes are available in all three main languages of Cape Town (Xhosa, Afrikaans, and English). I evolved the podcast methodology in a later stage of my praxis process as a form of member checking with contributors involved in various stages and aspects of the research. Once the four papers were written, I created a series of four short videos called In the Flow, with each video representing a translation of one of the four papers. I invited various contributors of the research project to either watch one or more of the In the Flow videos and/or read one or more of the academic papers, and then to respond in a Zoom call with me. The responses were then shared publicly in a series of seven Climate for Changing Lenses podcast episodes. Parts of these are included in a final song/music video called Please Don't Blow It. A Climate for Changing Lenses website was created to host all of this multimedia content that forms part of this thesis. A link to this website is provided in the Introduction section of this thesis. My research contributes to the advancement of knowledge in the areas of relational and reconciliation pedagogy, decolonising higher education, arts-based teaching, learning and research methodologies and the water-climate change nexus. My praxis process provided a relational model of reconciliation curriculum that has been tried and tested in two international contexts: Canada and South Africa.,Thesis (PhD) -- Faculty of Education, Education, 2021
Keywords: Environmental education -- South Africa; Environmental education Canada; Climatic changes in art; Water-supply Climatic factors; Decolonization; Reconciliation -- South Africa; Curriculum change; Traditional ecological knowledge